An Analysis of Illocutionary Acts Found in Kim Namjoon Speech (Leader of BTS) at the United Nation - Yovita Miftahsari Suseno; Pariyanto Pariyanto (Sintuwu Maroso Journal of English Teaching, 2022)
Kim Namjoon is the only representative of the Korean idol chosen by UNICEF to deliver a speech at the general assembly. BTS is of considerable concern to today's youth since its songs are evaluated as encouraging and helpful in the face of struggle. Thespeech entitled "Speak Yourself" is a persuasive speech that aligns with the aims of UNICEF's "Young Generation" mission in 2030. The purpose of this study is to identify the kinds of illocutionary acts used by Kim Namjoon and to know the actual functions of illocutionary force found in speech. A descriptive qualitative method is employed in this study to collect data and identify the illocutionary act by Searle and the context of thesituation by Halliday. The findings show 29 utterances containing illocutionary acts, which is representative 12 utterances, directive 7 utterances, expressive 8 utterances, and commissive 3 utterances. The actual functions of the utterances found by context situation analysis are representative: explaining, informing, reporting, claiming, and describing, expressive: thanking, expressing gratitude, expressions of happiness, expressing concern, despairing, and expressing sadness, directive: commanding, inviting, ordering, asking and requesting, commissive: promising.